Critical factors of green supply chain management on SMEs business performance Indonesia - Dewa, Parama Kartika (OPSI, 2024)
The COVID-19 pandemic has altered lifestyle and sparked a greater interest in GSCM. This study logically contributes to the branch of knowledge by demonstrating how resource-based attributes and integration can improve SME business performance while concurrently facilitating the successful transition from traditional to green supply chains. This study focused on batik SMEs that make their products using natural resources. The goal is to analyze SME performance models that affect GSCM, owner commitment, and supply chain connectivity. The data analyzed were gathered from a total of 163 experienced SME managers in the Special Region of Yogyakarta, Indonesia. PLS-SEM is the data analysis method used. The results validate that SME business performance is positively impacted by OC, SCC, and GSCM. The function of OC and SCC in SME business performance can also be mediated by GSCM.